Lactoferrin Has a Therapeutic Effect via HIF Inhibition in a Murine Model of Choroidal Neovascularization - Ibuki, Mari; Shoda, Chiho; Miwa, Yukihiro; Ishida, Ayako; Tsubota, Kazuo; Kurihara, Toshihide (Frontiers in Pharmacology, 2020)
Abstract (1) Background: Lactoferrin, a type of glycoprotein, is contained in exocrine fluids such as tears, breast milk, sweat, and saliva, and is known to have anti-microbial, antioxidant, and anti-cancer effects. In the ophthalmological field, topical administration of lactoferrin has been reported to have a therapeutic effect in a murine dry eye model. Hypoxia-inducible factor (HIF) regulates various gene expressions under hypoxia, including vascular endothelial growth factor (VEGF), and is considered as an alternative target for neovascular ocular diseases such as age-related macular degeneration (AMD). We previously screened natural products and identified lactoferrin as a novel HIF inhibitor. In this study, we confirmed that lactoferrin has an HIF inhibitory effect and a therapeutic effect in a murine model of neovascular AMD. (2) Methods: HIF inhibitory effects of lactoferrin were evaluated using a luciferase assay and western blotting in vitro. The quantified volume of choroidal neovascularization (CNV) induced by laser irradiation was compared with oral lactoferrin administration or conditional tissue specific Hif1a knockout mice. (3) Results: Lactoferrin administration showed a significant HIF inhibitory effect in the retinal neuronal cells. Oral administration of lactoferrin or conditional Hif1a gene deletion significantly reduced CNV volume compared to controls. (4) Conclusions: Lactoferrin has a therapeutic effect in a laser CNV model by suppressing the retinal HIF activity.